1994
DOI: 10.1152/ajpheart.1994.266.5.h1829
|View full text |Cite
|
Sign up to set email alerts
|

Effects of thapsigargin in normal and pretreated with ryanodine guinea pig cardiomyocytes

Abstract: We compared the effects of thapsigargin (TG), a selective blocker of Ca(2+)-adenosinetriphosphatase of sarcoplasmic reticulum (SR), and ryanodine (Ry) in the single isolated myocytes of guinea pig ventricular myocardium loaded with indo 1 acetoxymethyl ester (AM). TG (2 x 10(-7) M) inhibited the rapid phase of Ca2+ transient, increased time to peak intracellular Ca2+ concentration ([Ca2+]i) from 158 +/- 12 to 391 +/- 60 ms and decreased the total amplitude of the transient to 89 +/- 4% of the pre-TG control. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
1

Year Published

1996
1996
2002
2002

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 0 publications
3
10
1
Order By: Relevance
“…This is consistent with results in guinea-pig myocytes, where it has been shown that ryanodine (which increases SR Ca2+ loss), but not thapsigargin, can reduce the size of the beat [27]. [t has been suggested that Ca.z+ uptake by the SR curtails the rise in Ca2+ at the contractile apparatus.…”
Section: Discussionsupporting
confidence: 90%
“…This is consistent with results in guinea-pig myocytes, where it has been shown that ryanodine (which increases SR Ca2+ loss), but not thapsigargin, can reduce the size of the beat [27]. [t has been suggested that Ca.z+ uptake by the SR curtails the rise in Ca2+ at the contractile apparatus.…”
Section: Discussionsupporting
confidence: 90%
“…TBQ effects on AP duration are more probably explained by a smaller amount of SR released Ca2+ that would decrease the Na+/Ca2+ exchange current, a depolarizing current in rabbit ventricular cells (Bers, 1991 Another argument relies on the observation that in the rabbit and rat ventricle, TBQ, like CPA or TG, exerts a negative inotropic effect that was steady. We did not observe any reversal of the negative inotropic effect and we are not aware of such an effect with other inhibitors in multicellular preparations, whereas it has been reported in isolated guinea-pig (Lewartowski et al, 1994) or rabbit (Bassani et al, 1993; ventricular myocytes. As such a reversal is currently explained by abolition of trans-sarcolemmal Ca2" buffering by the SR, it is likely that a fraction of pumps unblocked by 30 uM TBQ is still able to buffer incoming Ca2".…”
Section: Specificity Of Tbqcontrasting
confidence: 66%
“…In fact, it has been shown that both compounds had a negative inotropic effect in most animal species, which could be expected on the basis of a decreased SR Ca2" content (Bassani et al, 1993;Lewartowski et al, 1994). However, paradoxical results have also been reported which showed that the shortening of TG-or CPA-treated ventricular myocytes from rabbit or guinea-pig had similar amplitude but a longer time course compared to control, despite an empty SR (Bassani et al, 1994;Lewartowski et al, 1994). This effect has been interpreted as the result of the suppression of the rapid SR buffering of incoming Ca2+which could then directly activate the contractile proteins, although at a slower rate compared to the rate at which Ca2" binds to the myofibrillar proteins when it is released from the SR (Janczewski & Lakatta, 1993).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…CPA and TG, which have been shown to inhibit sarcoplasmic reticular Ca2+-ATPase in skeletal and caridac muscles, are used as a tool for the study of excitation-contraction coupling in these muscles (Janczewski & Lakatta, 1993;Lewartowski et al, 1994;Chiesi et al, 1994;Yard et al, 1994). These drugs are also used in smooth muscle to deplete sarcoplasmic reticular Ca2+ or to inhibit Ca21 uptake by the sarcoplasmic reticulum (Sill et al, 1991;Low et al, 1991;Uyama et al, 1992;Low et al, 1992;Luo et al, 1993;Alexander & Cheung, 1994;Kwan et al, 1994;Naganobu et al, 1994).…”
Section: Discussionmentioning
confidence: 99%